Tyranny of the dominant shareholder : Hobson's choice before ONGC Board - Balasubramanian, N.; Barua, S. K. (Samir K.) ([London] : SAGE, 2016)
The case describes a situation where the government as the dominant majority shareholder in a listed Public Sector Enterprise (PSE) directs it through its executive Chairman (a government selected executive) to buy a part of government's stakes in another listed PSE, in which also the government is a majority shareholder.
Originally Published in: Barua, S. K., & Balasubramanian, N. (2015). Tyranny of the Dominant Shareholder: Hobson's Choice Before ONGC Board. BP0387. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Oil and Natural Gas Corporation Limited (India); Corporate governance -- Case studies; Government business enterprises -- Case studies; Nonprofit organizations -- Management -- Case studies